α-Skew π-McCoy Rings - Areej M. Abduldaim; Sheng Chen (Journal of Applied Mathematics)
As a generalization of α-skew McCoy rings, we introduce the concept of α-skew π-McCoy rings, and we study the relationships with another two new generalizations, α-skew π1-McCoy rings and α-skew π2-McCoy rings, observing the relations with α-skew McCoy rings, π-McCoy rings, α-skew Armendariz rings, π-regular rings, and other kinds of rings. Also, we investigate conditions such that α-skew π1-McCoy rings imply α-skew π-McCoy rings and α-skew π2-McCoy rings. We show that in the case where R is a nonreduced ring, if R is 2-primal, then R is an α-skew π-McCoy ring. And, let R be a weak (α,δ)-compatible ring; if R is an α-skew π1-McCoy ring, then R is α-skew π2-McCoy.